Reinvenções do cotidiano: análise dos regimes de sentido, interação e risco no gênero crônica - Sardas, Guilherme (2024)
Known for being a speech genre with great malleability in its structure, themes and approaches, the chronicle is consolidated in the Brazilian journalistic-literary tradition through an extensive range of styles and modes of updating. In this way, the genre provides the opportunity to investigate a complex dynamic of regimes of meaning, interaction and risk, according to the contributions of Eric Landowski, which reveal different practices and ways of life, as well as their underlying axiologies. The methodology is given by the semiotic analysis of chronicles by four Brazilian authors – José de Alencar, Machado de Assis, Rubem Braga and Danuza Leão –, who helped to construct and recreate the meanings of everyday experience in our culture. This work aims to fulfill two main objectives: to elucidate the procedures for apprehension and construction of meaning of different modalities of the chronicle genre for the elaboration of systematizations and didactic proposals, considering that it is a genre that, within the scope of the Brazilian education system, introduces the student to the examination of the literary text and its greater complexity in its meaning processes; in the theoretical field, to investigate the treatment of the concept of the speech genre in the Greimasian tradition and in sociosemiotics, starting from the observation that the topic of the speech genre has only been occasionally analyzed in the teachings of Greimas, in order to demand a development that becomes viable, under various aspects, by analyzing the regimes of meaning, interaction and risk. With these purposes, the thesis was intended to be a contribution to the examination of the chronic genre for the development of analytical and pedagogical practices